"[...] odstąpiłeś od twej pierwotnej miłości" (Ap 2, 4) - Sikora, Ryszard Adam (The Biblical Annals, 2017)
The author tries to find the answer what precisely is the reality in the Church of Ephesus that is described by the words: „you neglected your first love” (Rev 2, 4). He analyses the whole letter to the Church of Ephesus and makes many references to the whole of Revelation to show the meaning of the terms „love” and „the first”. In this Iight he realises that the formula of complaint (2, 4) says only about the love of the Church to Jesus Christ and that it refers to the first period of Christian life in Epfesus’ community.